The Influence Leader-Member Exchange and Work Culture on Elementary School Teacher Performance - Lina Rizki Hasyyati; Sugiarto Sugiarto; Masduki Ahmad (AL-ISHLAH: Jurnal Pendidikan, 2022)
Teacher performance has a huge influence on the achievement of education. This study aims to determine the effect of leader-member exchange and work culture on teacher performance in elementary schools throughout the Neglasari District, Tangerang City. The research method used a survey. Participants involved in the study were 110 teachers drawn from 24 schools in Neglasari District. Data were taken using a questionnaire. Data analysis technique using regression. The results of this study indicate that: (1) there is a direct positive influence of leader-member exchange on teacher performance, (2) there is a direct positive influence of work culture on teacher performance, and (3) there is a direct positive influence of leader-member exchange on work culture. So, it can be concluded that the quality of teacher performance is influenced by internal and external factors, such as work culture and leader-member exchange. The study results have implications for the work system in schools that must be built by school principals that are relevant to teacher competence.